Advancements on Single-Atom Catalysts-Mediated Persulfate Activation: Generating Reactive Species for Contaminants Elimination in Water - Wan Yu; Yin Xu (Molecules)
The single-atom catalyst (SAC) activated persulfate process has emerged as a highly efficient technology for eliminating refractory organic compounds in aqueous environments. This review delves into the intricacies of utilizing SACs for the effective removal of various contaminants in water. The common supports and the preparation procedures of SACs are summarized at first. The synthesis methods of SACs (i.e., wet chemical method, one-pot hydrothermal method, and high-temperature pyrolysis method) are also described. Then, a comprehensive overview of the diverse reaction mechanisms in SAC-activated persulfate systems is presented, including a radical oxidation process via sulfate or hydroxyl radicals and superoxide radicals, or a nonradical process via single oxygen, surface active complex, and high-valent metal-oxo species oxidation. The impact of key factors such as peroxides concentration, SAC dosage, reaction pH, inorganic anions, organic matter, operando stability, and real water is also delved. The removal of various pollutants (i.e., azo dyes, phenolic compounds, pharmaceuticals, and bacteria) by this process is further summarized. Finally, the challenges and perspectives in the field of water treatment utilizing SACs are discussed.